Islamic Work Ethics in Indonesia Islamic Microfinance Institutions: A Bibliometric Review and Analysis - Christiyanto, Wenda Wahyu; Hadi Senen, Syamsul; Rofaida, Rofi (SHAHIH: Journal of Islamicate Multidisciplinary, 2022)
The concept of "Islamic Work Ethics at Islamic Micro Finance Institutions in Indonesia" is a development of "Islamic work ethics", studied and applied in sharia-based microfinance institutions, especially those in Indonesia, considering that Indonesia is the most prominent Islamic country in the world. This paper provides an extensive bibliometric literature overview on "Islamic Work Ethics at Islamic Micro Finance Institutions in Indonesia". Publish or Perish (PoP) software found articles related to the topic, with a database sourced from Google Scholar. 596 of the 990 articles from 2015 to 2020 were analyzed from Google Scholar's database. The selected references are managed using reference manager software, Mendeley. After processing Google Scholar's database, this paper orders and imagines it utilizing VOSviewer. In general, this paper gives an incredible reference highlight for future research on "Islamic Work Ethics at Islamic Micro Finance Institution in Indonesia".